Analysing the Importance-Competence Gap of Distance Educators With the Increased Utilisation of Online Learning Strategies in a Developing World Context - Bezuidenhout, Adéle (International Review of Research in Open and Distributed Learning, 2018)
The competence of distance educators has a significant impact on learners’ success. The paradigm shift for universities to become distance and electronic learning environments justifies the urgency to address competency gaps in distance educators’ competencies efficiently. From a strategic human resource development perspective, the systems theory is used to explain the idea of maximising outputs with the minimum inputs (Biddle, 1986). In this study, distance educators at Unisa reflected on their experienced competency gaps. Where previous studies mainly focus on the size of the gaps, the aim of this article is to highlight the competency gaps likely to have the biggest impact. For this study, we used stratified non-probability sampling, and selected 407 academics who were, at the time of the study, permanently employed at a mega ODL university in South Africa. These academics represented a wide range of colleges, campuses, ages, and genders. The results of this study have implications for capacity building of academic staff in developing world contexts and other contexts where resources are scarce.